Concurrent Escherichia coli tubo-ovarian abscess and Campylobacter jejuni gastroenteritis: A case report - Alison Laura King; Nicole Stamatopoulos (Elsevier, 2020)
Haematogenous or direct spread of bacterial infection causing pelvic inflammatory disease of the upper female reproductive tract is uncommon. We report a diagnostically challenging case of a 41-year-old woman with a background of Stage 4 endometriosis presenting with fever, diarrhoea and abdominal pain with recent history of pyelonephritis. Initially managed for undifferentiated abdominal pain with unclear focus of infection, a broad range of investigations were undertaken. Laboratory samples confirmed the presence of Campylobacter jejuni and appropriate treatment for Campylobacteriosis was commenced. Despite treatment, her condition deteriorated and repeat radiological imaging revealed bilateral tubo-ovarian abscess requiring surgical drainage for control of severe sepsis. Sterile surgical samples of the abscess revealed Escherichia coli. This case adds to the growing body of evidence of the association between pelvic inflammatory disease, severe endometriosis and development of tubo-ovarian abscess. Sepsis associated with tubo-ovarian abscess has a mortality rate of up to 10%. Hence, we present this case to highlight severe endometriosis as a risk factor for disease and the need for prompt reassessment of the deteriorating woman with sepsis and pelvic pain to direct efforts to minimise morbidity and mortality. Keywords: Tubo-ovarian abscess, Pelvic inflammatory disease, Sepsis, Endometriosis